Tanggapan dan harapan masyarakat terhadap penulisan berita di media arus perdana di Malaysia / Mohd Syuhaidi Abu Bakar and Nur Shakila Hussain @ Othman - Abu Bakar, Mohd Syuhaidi; Hussain @ Othman, Nur Shakila (2019)
Given the existing trend in which alternative media sources and mainstream media sources are in a constant tug of war, people will continue to hear about mainstream media for a long time to come. Together, these networks and publications cater to the majority of the population. They control what most people hear, see and read. For this reason, a lot of dissenters have likened them to puppeteers and questioned their impartiality in delivering the truth. However, most mainstream media outlets are biased right or left but pretended to be neutral. Same goes to mainstream media outlets in Malaysia. This study was done to identify the perception and hopes towards news being produced by mainstream media outlets in this country. Data was collected from 201 (n=201) Malaysians using purposive sampling and was analyzed with statistical analysis (SPSS) using descriptive analysis. Findings where represented by percentages. The findings of this paper advocate that majority of the respondents supports local mainstream media outlets. Locally, mainstream media is considered to be a more credible news source than alternative media, however respondents urges the government to tightened the media-related policies and laws in Malaysia.